Plot size under field conditions to determine soybean agronomic characteristics - Belmonte, Cristiani; Vasconcelos, Edmar Soares de; Strenske, Andressa; Lorenzetti, Eloisa (Scientia Agraria Paranaensis, 2020)
Within the field of performance of agricultural experimentation we have some obstacles related to conducting experiments, the biggest of which is the comparison between treatments with the greatest possible precision, in order to arrive at safe conclusions from the observed results. The objective of this work was to evaluate the relationship between the plot sizes and the stand determination, height at maturation, as well as soybean yield. Three areas were cultivated with soybean for this purpose. In the plant stand determination 18 plot sizes were tested, at the plant height at maturation 14 sizes were tested, and 10 sizes were tested for productivity. The characteristics measurement was performed in triplicate for each plot size, randomly distributed within each area. The characteristic mean for each plot size allowed the adjustment subjective of two regression models, one facing up and one facing down. At the point where the difference among the adjusted models reached the value of the sample standard deviation, the ideal minimum plot size was determined. The evaluation of 14.3 linear m is required in the soybean plants stand determination. It is necessary to quantify 26 plants to guarantee an ideal estimate of the soybean plants at maturity height. It is necessary crop 22 m2 plot to safeguard an ideal estimate of soybean yield.